The Perception of Angkolanese toward Mosques Fund Deposit on Mosque Administrator House at West Angkola District, North Sumatera - Arbanur Rasyid; Muhammad Wandisyah R Hutagalung; Desi Widia Pernanda SMJ (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2020)
The problem in this study was a decision by the mosque management not to use the services of Islamic banks in saving mosque funds. The formulation of the problem in this study described on how the public perception of West Angkola Subdistrict on the deposit of mosque funds in the house of mosque administrators and what factors caused mosque administrators to make decisions by saving mosque funds in the administrator house. This study discussed the perceptions of the people of West Angkola District on the storage of mosque funds in the house of the mosque management. This research was a qualitative study using primary data with 60 samples. Data collection techniques were interviews, observation, namely observing an event in the field. The results of the study indicated that the perceptions of the people of West Angkola Subdistrict on the deposit of mosque funds in the house of the mosque administrator had a positive perception of the decision of mosque administrators in saving mosque funds. The community had high confidence in the decision of the mosque management in managing mosque funds. One of the factors influencing the decision to make mosque funds in the mosque administrator house was the sense of public trust in the mosque administrators in saving funds. Besides, the distance that is quite far and the mosque management's knowledge is lacking on Islamic banks affected the decision of mosque administrators to save mosque funds.